Creating Time: Social Collaboration in Music Improvisation. (20th November 2017) - Walton, Ashley E.; Washburn, Auriel; Langland‐Hassan, Peter; Chemero, Anthony; Kloos, Heidi; Richardson, Michael J.
Abstract: Musical collaboration emerges from the complex interaction of environmental and informational constraints, including those of the instruments and the performance context. Music improvisation in particular is more like everyday interaction in that dynamics emerge spontaneously without a rehearsed score or script. We examined how the structure of the musical context affords and shapes interactions between improvising musicians. Six pairs of professional piano players improvised with two different backing tracks while we recorded both the music produced and the movements of their heads, left arms, and right arms. The backing tracks varied in rhythmic and harmonic information, from a chord progression to a continuous drone. Differences in movement coordination and playing behavior were evaluated using the mathematical tools of complex dynamical systems, with the aim of uncovering the multiscale dynamics that characterize musical collaboration. Collectively, the findings indicated that each backing track afforded the emergence of different patterns of coordination with respect to how the musicians played together, how they moved together, as well as their experience collaborating with each other. Additionally, listeners' experiences of the music when rating audio recordings of the improvised performances were related to the way the musicians coordinated both their playing behavior and their bodily movements. Accordingly, the study revealed how complex dynamical systems methods (namely recurrence analysis) can capture the turn‐taking dynamics that characterized both the social exchange of the music improvisation and the sounds of collaboration more generally. The study also demonstrated how musical improvisation provides a way of understanding how social interaction emerges from the structure of the behavioral task context. Abstract : Musical improvisation is a natural case of human pattern formation, and Walton and colleagues investigate the way that different contextual constraints affect patterns of improvisation and their aesthetic quality. The authors find that coordination patterns are more diversified between two musicians when the musical space in which to improvise is relatively more constrained. They also find that listeners experience more diversified, complementary patterns between musicians as more enjoyable and harmonious.